The Effectiveness of Non-Benzodiazepine, Non-Barbiturate Medications for Alcohol Withdrawal Syndrome: A Rapid Systematic Review. (3rd December 2020) - Ghosh, Abhishek; Mahintamani, Tathagata; Choudhury, Shinjini; Sharma, Nidhi; Das, Sauvik
Abstract: Aim: There are potential clinical, ethical and legal concerns with overdosing benzodiazepines (or barbiturates) for the treatment of moderate to severe alcohol withdrawal symptoms (AWS) through telemedicine or ambulatory outpatients. A rapid systematic review to (a) qualitatively summarize the non-benzodiazepine treatment alternatives, (b) evaluate the quality of evidence for the same to effectively manage moderate to severe AWS. Methods: We conducted searches on PubMed (January 1990 to 31 March 2020), Cochrane Central Register of Controlled Trials, and Google Scholar. We selected the English language randomized controlled trials (RCTs) assessing the efficacy and adverse effects of non-benzodiazepine and non-barbiturate medications among adults with a diagnosis of AWS. Data extraction was done in a predefined format. Risk of bias (RoB) assessment and qualitative synthesis of evidence was done with the RoB2 tool and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) proGDT. Results: Thirty-four RCTs were included. Gabapentin ( n  = 6), carbamazepine ( n  = 5), baclofen ( n  = 5), valproate ( n  = 3), clonidine/lofexidine ( n  = 3) and acamprosate ( n  = 2) had more than one trial with a particular comparison group. Four studies were found to have a low ROB. The GRADE evidence summary showed gabapentin had a 'moderate' level of evidence against standard benzodiazepine treatments for reducing the severity of AWS. The level of certainty was 'low' for carbamazepine, baclofen and valproate and 'very low' for acamprosate and clonidine/lofexidine. Reported adverse events between these alternative medications and benzodiazepines or placebo were generally unremarkable. Conclusions: Although benzodiazepines remain the treatment of choice for AWS, during particular circumstances, gabapentin could be an alternative although like benzodiazepines is not without risk when used in the community. Future RCTs must aim to improve upon the quality of evidence.